Derivation of trophoblast stem cells from naïve human pluripotent stem cells - Dong, Chen (eLife, 2020)
Naïve human pluripotent stem cells (hPSCs) provide a unique experimental platform of cell fate decisions during pre-implantation development, but their lineage potential remains incompletely characterized. As naïve hPSCs share transcriptional and epigenomic signatures with trophoblast cells, it has been proposed that the naïve state may have enhanced predisposition for differentiation along this extraembryonic lineage. Here we examined the trophoblast potential of isogenic naïve and primed hPSCs. We found that naïve hPSCs can directly give rise to human trophoblast stem cells (hTSCs) and undergo further differentiation into both extravillous and syncytiotrophoblast. In contrast, primed hPSCs do not support hTSC derivation, but give rise to non-self-renewing cytotrophoblasts in response to BMP4. Global transcriptome and chromatin accessibility analyses indicate that hTSCs derived from naïve hPSCs are similar to blastocyst-derived hTSCs and acquire features of post-implantation trophectoderm. The derivation of hTSCs from naïve hPSCs will enable elucidation of early mechanisms that govern normal human trophoblast development and associated pathologies.